Keefektifan Dosis Koagulan Feri Klorida (Fecl3) Dalam Menurunkan Kadar Total Suspended Solids (Tss) Pada Air Limbah Batik Brotoseno Masaran Sragen - Norjannah, Siti, Dwi Astuti, SKM., M.Kes, Haru Subaris Kasjono, SKM., M. Kes (2015)
TSS (Total Suspended Solids) a certain volume of sample is filtered through a glass fiber filter previously cleaned and weighed. Filters were then rinsed and dried at a temperature of 103-105 ° C in an oven. Changes in the weighting filter is the weight of suspended material .. The results of measurements of the levels of TSS Brotoseno batik waste water at 203.5 mg / l. This value exceeds a predetermined quality standards. The purpose of this study was to determine the coagulant dose of ferric chloride (FeCl3) is most effective at lowering levels of TSS in wastewater of batik. This type of research is true experiment with pretest posttest study design with control group. Population of this research is Brotoseno batik waste water generated from the entire process of traditional batik processing and the sampling technique using a quota sampling. Statistical test using One Way Anova with data analysis p = 0.000 (p <0.01), so that Ha accepted, which means that there is the most effective dose of the addition of FeCl3 coagulant dose in lowering levels of TSS in wastewater of batik. Obtained the highest decline of 94.51%. (147.16 mg / l) at a dose of 2.5 g / l.